Potensi Urin Sapi dan Rock Phosphat Terhadap Produksi Benih Tanaman Alfalfa (Medicago sativa L) - Renan Subantoro; Rossi Prabowo (Universitas Wahid Hasyim, 2012)
Alfalfa is often referred to as medic purple or lucerne was originally a wild plant that comes from the forest, before the cultivated by humans. Habitat cultivated by native plants are located in the Mediterranean mountains in southwest Asia Asia. From this plant was introduced to Europe by the Persians around the year 490 SM. Rock phosphate is a natural fertilizer that can be obtained easily in Indonesia and has a phosphorus content which can be used as an alternative to the relatively expensive TSP fertilizer and phosphorus are the elements that affect the growth and crop production. Cow urine and rock phosphate have the potential to used as a source of nutrients for growth and development of alfalfa flower and seed . Key word: alfalfa, rock phosphate, cow urine, flowers and seeds